Pengaruh Kelor Dan Bakteri Asam Laktat Isolat Nira Lontar Terhadap Gambaran Eritrosit Dan Trombosit Ayam Broiler - Aska Adhitama Fanmira; Frans U Datta; Annytha I. R Detha; Nancy D.F.K Foeh; Nemay Ndaong (Jurnal Veteriner Nusantara, 2022)
Broiler chicken is one of the primary protein sources for humans, where the need for broiler chickens is increasing from year to year. For this reason, innovation is needed in producing complete feed for broiler chickens using local resources from NTT, namely Moringa. Moringa is very good given as feed for broiler chickens because Moringa contains essential nutrients needed for the growth and development of broiler chickens. Besides Moringa, many lactic acid bacteria to animal feed will be able to increase the absorption of nutrients from feed because it can suppress the growth of pathogenic bacteria, which can be seen from the picture of erythrocytes and platelets. The purpose was to analyze the effect of lactic acid bacteria isolated lontar palm sap on the erythrocyte and thrombocyte profile in broiler chickens. The feed was given as much as 3 kg per day with the administration time in the morning and evening. The provision of feed containing Moringa and lactic acid bacteria isolates lontar palm sap to broiler chickens did not statistically show a significant difference between the control group and the treatment group. But descriptively, it can be seen that on day ten, the erythrocyte value in the treatment group was higher than in the control group. In contrast, on day 21, the erythrocyte value in the treatment group was lower than in the control group. Provision of feed containing Moringa and lactic acid bacteria isolates palm sap to broiler chickens did not statistically show an effect but descriptively showed a difference in the average platelet value. The average platelet value in the treatment group was higher than in the control group. Further research needs to be done with a larger sample size related to Moringa as feed for broiler chickens.